KRITIK SASTRA FEMINISME PADA CERPEN ‘SI PUCUK KALUMPANG’ KARYA AJIP ROSIDI - Indira, Indira Intan Pratiwi (Hasta Wiyata, 2024)
Literary criticism is the science of literature that studies, examines, considers, and assesses the strengths, weaknesses, and merits of a literary work. Literary works are created as the author's statement to others. The values in literary works are realized in the minds of readers through experiences and ways of thinking, including idealism. In this study, researchers are interested in analyzing deixis in the novel "Si Pucuk Kalumpang" by using data collection techniques in the form of observation and documentation. Feminist Literature In the story "Si Pucuk Kalumpang" tells how a mother tries to defend her child, and how women who are often considered weak, become very strong and tough characters like men. There are three streams of feminism found in the story Pemeksi Air Mata by Agus Noor, namely social feminism, marxist feminism, and social liberal streams